1995
DOI: 10.1111/j.1751-1097.1995.tb09247.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Damage in Yeast Cells Caused by Photodynamic Treatment With Toluidine Blue

Abstract: The positively charged photosensitizer toluidine blue (TB) can induce loss of clonogenicity in Kluyveromyces marxianus. Previous studies have revealed that, as a consequence of the localization of this dye at the cell surface, photodynamic action results in extensive damage at the level of the plasma membrane. In this paper, a study is reported on the effect of photodynamic treatment with TB on intracellular enzymes. It is shown that treatment with TB and light resulted in the inhibition of alcohol dehydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Our observations are very similar to those obtained for the PDI of K. maxianus with toluidine blue (30,31) and the PDI of C. albicans with hematoporphyrin (3,4). In both cases it was concluded that the plasma membrane became permeable during PDI, but the cell inactivation was attributed to more subtle forms of membrane damage, followed by damage to intracellular targets.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our observations are very similar to those obtained for the PDI of K. maxianus with toluidine blue (30,31) and the PDI of C. albicans with hematoporphyrin (3,4). In both cases it was concluded that the plasma membrane became permeable during PDI, but the cell inactivation was attributed to more subtle forms of membrane damage, followed by damage to intracellular targets.…”
Section: Discussionsupporting
confidence: 76%
“…In order to optimize the PDI of microorganisms, knowledge of the underlying mechanisms is indispensable. However, in the majority of studies investigating the mechanisms of yeast PDI, the anionic hematoporphyrin and its derivatives (3,39), the hydrophobic chloroaluminum phthalocyanine (29,32) or the cationic thiazine dye toluidine blue (6,13,28,30), are used as photosensitizers.…”
mentioning
confidence: 99%
“…Cellular metabolism can be reduced after APDI due to decreased transport of carbohydrates, amino acids, or phosphate through membrane-bound carrier proteins (30). Photodynamic action can also disturb carbon metabolism and ATP production by knocking out intracellular enzymes (e.g., alcohol dehydrogenase, glyceraldehyde-3-phosphate dehydrogenase, hexokinase, and cytochrome c oxidase) (31). In addition, photodynamic damage of mitochondria can increase the expression of p21, an inhibitor of cyclin-dependent kinases, leading to growth inhibition (29).…”
Section: Discussionmentioning
confidence: 99%
“…PDT can be defined as eradication of target cells by reactive oxygen species (ROS) produced by means of a photosensitizing compound and light of an appropriate wavelength (6). Although PDT is more widely known for its application to the treatment of neoplasms, there is also interest in antimicrobial PDT, as a large number of microorganisms (including oral species) have been reported to be killed in vitro by this approach (21,27,31,40,43,46,47). Furthermore, the potencies of some key virulence factors (lipopolysaccharide and proteases) have also been shown to be reduced by photosensitization (18,32).…”
mentioning
confidence: 99%